Grundlegende Untersuchungen zur Erfassung der realen Vorspannung von armierten Kaltfließpresswerkzeugen mittels Ultraschall - Putz, Alexander (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2006)
This book presents the development of a measurement System based on ultrasonics for the Evaluation of the real prestressing conditions of shrunken Cold forging Tools. This enables the securing of prestressing conditions that have a significant influence on tool life already before the usage in the pres